2016
DOI: 10.1016/j.jad.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and treatment-seeking for depression in a multilingual worldwide sample

Abstract: Background Prior research has found higher rates of mental health problems among sexual minority individuals. We examine treatment-seeking for depression, as well as its relationship with sexual orientation, in a large, multilingual, international sample. Method Participants in an automated, quintilingual internet-based depression screening tool were screened for depression, and completed several background measures, including sexual orientation (with an option to decline to state) and past and current depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Indeed, factors that have been linked to substance use among sexual minorities, such as lower self-efficacy (Tucker et al, 2008), as well as lower life satisfaction and higher stress levels, especially related to the coming out process (Padilla et al, 2010; Rosario et al, 2009; Schauer et al, 2013), may explain why sexual minority youth would be less likely to possess alternative coping resources such as accessing therapy, or engaging in activities like arts or sports. Accordingly, and relatedly to the hypothesized relationship between cannabis use and depression symptoms as a reflection of internalized homophobia posited above, one study found that participants who declined to disclose their sexual orientation were more likely not to seek treatment for their depression (Rutter et al, 2016). This is detrimental in light of the current findings identifying depression symptoms as an important precursor of cannabis use in this group.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, factors that have been linked to substance use among sexual minorities, such as lower self-efficacy (Tucker et al, 2008), as well as lower life satisfaction and higher stress levels, especially related to the coming out process (Padilla et al, 2010; Rosario et al, 2009; Schauer et al, 2013), may explain why sexual minority youth would be less likely to possess alternative coping resources such as accessing therapy, or engaging in activities like arts or sports. Accordingly, and relatedly to the hypothesized relationship between cannabis use and depression symptoms as a reflection of internalized homophobia posited above, one study found that participants who declined to disclose their sexual orientation were more likely not to seek treatment for their depression (Rutter et al, 2016). This is detrimental in light of the current findings identifying depression symptoms as an important precursor of cannabis use in this group.…”
Section: Discussionmentioning
confidence: 98%
“…Although we view our sample of men who screened positive for depression as a strength to our study, we also recognize the limitations of our mostly white, mostly heterosexual sample, who tended to have some college education, and all had Internet access. Research shows help-seeking for depression differs as a function of many variables including race, ethnicity, and education (Magaard et al, 2017), as well as sexual orientation and language use (Rutter et al, 2016). Even the relationship between stigma and help-seeking differs between racial groups with internalized stigma reported to mediate the relationship between public stigma and attitudes toward mental health treatment for white persons but not Black persons (Brown et al, 2010).…”
Section: Limitationsmentioning
confidence: 99%
“…The literature indicates that young people who belong to sexual minorities are significantly more likely to present depressive symptoms and face the double stigma of belonging to this marginalized group and experiencing mental health problems 30,31 . This disparity in the prevalence of depressive symptoms among non-heterosexual individuals has been associated with stressors such as discrimination, structural prejudices, concealment of sexual orientation, and isolation among heterosexual individuals 32,33 .…”
Section: Discussionmentioning
confidence: 99%